Função simbólica em pessoas com Transtorno do Espectro Autista: requisitos comportamentais para a formação de classes de equivalência - Varella, André Augusto Borges (Universidade Federal de São Carlos, 2013)
Individuals with autism present language impairments and different degrees of difficulty in discriminative learning. From the standpoint of language as symbolic behavior, language impairments could be related to individuals discriminative repertoires, which may not support rapid acquisition of arbitrary relations and equivalence class formation. The objective of the present work is to investigate possible relations between discriminative repertoires and equivalence class formation in individuals with autism. The first chapter consists in a review of empirical studies about the ABLA test, used to assess the ease or difficulty in learning tasks that require the establishment of different types of discriminations. The chapters 2 and 3 presents two empirical studies, which investigated the role of discriminative repertoires and the relations between the types of discriminations taught and tested (intra-modal and cross-modal) on equivalence class formation. In Study 1, AA, BB and CC identity relations, with class-specific compound consequences (tangible + auditory stimulus) were taught to three autistic participants who failed the ABLA predictive tasks of arbitrary conditional discriminations, and to four participants who passed the predictive tasks. Tests were conducted to assess AB, BA, AC, CA, BC and CB relations. Evidence of equivalence class formation was obtained for one of three individuals who failed the predictive tasks and for three of four individuals who passed the ABLA tasks. In the Study 2, AB and CD visual relations with class-specific compound consequences (tangible + auditory stimulus) were taught to four participants. The visual-visual relations BA, DC, AC, CA, AD, DA, BC, CB, BD and DB and auditory-visual relations SA, SB, SC and SD were tested. All participants showed emergence of all auditory-visual relations and only one participant did not show the emergence of all visual-visual relations. The results suggest an important role of discriminative repertoires on equivalence class formation and demonstrate that auditory-visual relations (cross-modal) can emerge after teaching visual-visual conditional discriminations (intra-modal), if auditory stimuli are employed as class-specific consequences. The implications of these results for teaching symbolic repertoires and its requisites to individuals with autism are discussed.
Symbolic function in individuals with Autism Spectrum Disorder: behavioral requisites for equivalence class formation
Keywords: Psicologia experimental; Autismo; Equivalência de estímulos; Discriminação condicional; Discriminação simples; Pré-requisitos; Stimulus equivalence; Conditional discrimination; Simple discrimination; Prerequisites; Autism; CIENCIAS HUMANAS::PSICOLOGIA